Exploring the Link between Supply Chain Agility, Supply Chain Cost, Supply Chain Responsiveness, Global supply Chain Risk Management, and Contribution in Global Manufacturing: An Indonesian Perspective - Arifin, Agus Zainul; Yanuar, Yanuar; M.N, Nuryasman (International Journal of Supply Chain Management, 2018)
During last decade, supply chain management has emerged as a key for sustainable completive advantages. Increasing globalization has given birth to new philosophies and businessman has started focusing on the new ways of occupying market share. However, the share of Indonesia in global production has decreased from 31.953% in the start of this year to 20% in 2017. Which shows a gradual decrease of 11% in 16 years. To address this issue, the ultimate objective of this study is to develop a framework to boost global manufacturing through supply chain activities. This objective was achieved by examining the effect of supply chain agility, effective supply chain cost, supply chain responsiveness and risk management practices. Survey questionnaires was used to collect the data and PLS SEM used to analyze the data. It is found that supply chain agility, effective supply chain cost and supply chain responsiveness has significant positive effect on global manufacturing. Moreover, risk management practices as a moderating variable strengthen this effect and enhances the global manufacturing activities.